Which factors influence psychiatric diagnosing in substance abuse treatment? - Wynn, Rolf; Landheim, Anne; Hoxmark, Ellen Margrethe (International Journal of Mental Health Systems, 2013)
The importance of diagnosing and treating co-occurring psychiatric disorders among substance abusers in treatment has received much attention. The aim of this study was to investigate to which extent co-occurring psychiatric disorders are diagnosed in a clinical population of substance abusers, and which factors (including the use of MINI-Plus) that influence the diagnosing of co-occurring psychiatric disorders. Patients (N = 275) who received inpatient substance use treatment in five different units in Northern Norway participated in the study. The patients’ clinicians gave information on diagnoses given during the stay in the units, and whether a systematic diagnostic tool was used for the diagnosing (MINI-Plus). Predictors of independent co-occurring psychiatric disorders were examined utilizing hierarchical regression analysis. One third of the patients were given an independent psychiatric diagnosis. Less than half of the patients were assessed using a diagnostic tool. The main predictor of diagnosing of independent psychiatric disorders was the use of the diagnostic tool MINI-Plus. Younger patients and patients that used less alcohol, were given independent psychiatric diagnoses more frequently. The number of co-occurring independent psychiatric diagnoses was lower compared to other studies using standardized diagnostic tools. The low number of patients assessed by such a tool, and the strong relationship between the use of such a tool and the diagnosing of co-occurring psychiatric disorders, suggest that the implementation of standardized diagnostic tools should be addressed in the units. Generally, patients suffering from substance use disorders should be systematically screened for other psychiatric disorders, in order to improve their treatment and health.